Preparation method of high-strength and high-conductivity Cu-Cr-Zr alloy wire
Through multi-stage thermal mechanical treatment methods, including vacuum smelting, homogenization annealing, die forging, solid solution treatment, pre-aging treatment, drawing and multiple aging treatments, the problems of fast diffusion rate of Cr elements and nano-level Cr particles being sensitive to temperature and time during the processing and preparation of Cu-Cr alloy wires are solved, and the high temperature stability and precipitation uniformity of the alloy are achieved, and the strength and conductivity are improved.
Patent Information
- Application Number
- CN202510042064.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
During the processing and preparation of precipitation-strengthening Cu-Cr-Zr alloy wire, the Cr element diffusion rate is fast, and nano-scale Cr particles are sensitive to temperature and time, which easily lead to excessive aging, resulting in severe changes in strength, difficult control and uneven performance.
Multi-stage thermal mechanical treatment methods are adopted, including vacuum smelting, homogenizing annealing, die forging, solid solution treatment, pre-aging treatment, drawing and multiple aging treatments, and the microstructure and performance of the alloy are gradually optimized through these steps.
It significantly improves the high-temperature stability and precipitation uniformity of the alloy, delays the coarseness of nano-scale chromium particles, improves the strength and conductivity of the alloy, and ensures the stability and uniformity of material properties.
Smart Images

Figure CN119824258A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy preparation, and in particular relates to a multi-stage thermomechanical treatment preparation method for a high-strength and high-conductivity Cu-Cr-Zr alloy wire. Background Art
[0002] Cu-Cr-Zr alloys are widely used in applications requiring high strength and conductivity, such as high-strength wires and resistance welding electrodes, due to their excellent electrical, thermal, and mechanical properties. The Cr and Zr elements added to this alloy have significant solubility differences at high and low temperatures. Therefore, through solution treatment and subsequent aging, nanoscale second-phase particles can be dispersed and precipitated in the matrix, purifying the solute elements dissolved at high temperatures. This results in high strength, high conductivity, and wear resistance, and is currently widely used on high-speed rail lines such as the Beijing-Shanghai, Beijing-Tianjin, Beijing-Zhangjiakou, and Chengdu-Chongqing lines. However, during the processing and preparation of precipitation-strengthened Cu-Cr-Zr alloy wires, the diffusion rate of Cr in the copper matrix is very fast. The precipitated nanoscale Cr particles are very sensitive to temperature and time, with a rapid precipitation rate. This makes overaging very likely, leading to drastic strength variations. Therefore, control during production is difficult, and uneven performance is a common problem.
[0003] A search revealed a Chinese patent document that discloses a high-ductility, high-strength, and high-conductivity CuCrZr-based copper alloy and its preparation method [Application Number: 201911111463.4, Publication Number: CN110747365A]. This preparation process involves solution treatment followed by direct cold deformation and aging, which improves the copper alloy's properties by grain refinement. However, this process is prone to dislocations and the accumulation of precipitated phases at grain and subgrain boundaries, resulting in uneven alloy properties. A search revealed a Chinese patent document that discloses a method for preparing a CuCrZr alloy [Application Number: 201610293159.6, Publication Number: CN105925922A]. This preparation process primarily involves continuous equal-channel angular extrusion, enabling the preparation of alloys exceeding 1000 m in length and exhibiting reasonable high performance. However, the complex process is not conducive to industrial production, and the uniformity of the alloy's internal properties is not emphasized.
[0004] After searching, it was found that Chinese patent literature disclosed a method for preparing CuCrZr alloy by a double-stage aging process [Application Number: 202111201564.8, Publication Number: CN113832367A]. Its preparation process is to perform two aging processes directly after cold deformation. The main purpose is to have a certain strength while improving the elongation of the alloy. However, its process uses a low-temperature aging method after cold rolling deformation to make the precipitated phase uniformly precipitate in the matrix, resulting in the final CuCrZr alloy not having very high performance. Summary of the Invention
[0005] A method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire comprises the following steps:
[0006] The alloy raw material includes the following components by mass percentage: 0.30%-0.40% chromium, 0.10%-0.25% zirconium, 0.02%-0.12% magnesium, 0.01%-0.05% silicon, 0.05%-0.25% hafnium, and the balance is copper and unavoidable impurities.
[0007] Step 1: Place the alloy raw materials into the melting furnace according to the proportion and perform vacuum melting;
[0008] Step 2: Casting the liquid molten alloy obtained in step 1 to obtain a cylindrical ingot;
[0009] Step 3: performing homogenization annealing on the cylindrical ingot obtained in step 2 to obtain a homogenized cylindrical ingot;
[0010] Step 4: The cylindrical ingot obtained in step 3 is subjected to surface treatment and then die forged to obtain an alloy rod;
[0011] Step 5: performing a solution treatment on the alloy rod obtained in step 4 to obtain a solution treated alloy rod;
[0012] Step 6: Performing a pre-aging treatment on the alloy rod obtained in step 5 to obtain an alloy rod with a certain strength;
[0013] Step 7: Drawing the alloy rod obtained in step 6 for the first time to obtain alloy wire;
[0014] Step 8: subjecting the alloy wire obtained in step 7 to a second aging treatment to obtain an aged alloy wire;
[0015] Step nine: Drawing the alloy wire obtained in step eight for a second time to obtain a second-drawn alloy wire;
[0016] Step 10: The alloy wire obtained in step 9 is subjected to a third aging process, and the finished alloy is obtained after surface treatment to obtain a high-strength and high-conductivity alloy wire.
[0017] Preferably, in the vacuum melting process of step 1, the melting temperature is 1200°C-1400°C, the holding time is 0.5h-2h, the melting furnace is evacuated to a vacuum, and then high-purity argon is slowly introduced at a flow rate of 10-50 L / min until an inert protective atmosphere is formed in the furnace, and the pressure is maintained at or slightly above atmospheric pressure. A continuous flow of argon is maintained throughout the melting process.
[0018] Through the above technical solution, during the vacuum melting process, the furnace is first evacuated to a vacuum, effectively removing residual oxygen, moisture, and other reactive gases within the furnace, significantly reducing the risk of oxidative impurities or harmful gas contamination introduced during the melting process. High-purity argon is then slowly introduced, with the argon flow rate controlled at 10-50 L / min, to ensure a stable inert protective atmosphere within the furnace and maintain the melting environment pressure at or slightly above atmospheric pressure. Throughout the melting process, the continuous flow of argon forms a protective barrier for the melt, effectively isolating the molten copper alloy from contact with the outside air, thereby suppressing the occurrence of oxidation reactions and preventing the formation of oxide inclusions in the alloy.
[0019] Preferably, in the casting process of step 2, the casting temperature is 1100° C.-1300° C., and the diameter of the cast cylindrical ingot is 90 mm.
[0020] Through the above technical solution, during the casting process, the casting temperature is controlled within the range of 1100℃-1300℃, ensuring that the melt has good fluidity and appropriate supercooling, and avoiding surface defects or internal defects of the ingot caused by insufficient temperature, such as cold shut, porosity and pores. At the same time, temperature control within this range also effectively prevents the problems of coarse grains and element burnout caused by excessive temperature, ensuring the density of the internal structure of the ingot and the uniformity of the composition. In addition, by preferably setting the diameter of the cylindrical ingot to 90mm, this size design is not only suitable for rapid and uniform cooling, reducing thermal stress and crack risks during the casting process, but also provides a suitable raw material morphology and size basis for subsequent homogenization annealing, forging and processing steps. The optimized casting process combined with a reasonable ingot size greatly improves the quality of the casting and the efficiency of subsequent processing, thereby ensuring the high strength and high conductivity of the final product.
[0021] Preferably, in the homogenization annealing process of step three, the treatment temperature is 900° C.-950° C., and the holding time is 4 h-6 h.
[0022] Through the above technical solution, in the homogenization annealing process, the treatment temperature is preferably set to 900℃-950℃, and the holding time is set to 4h-6h. Through the precise control of this process parameter, the composition and structure homogenization of the ingot can be effectively promoted. Within the temperature range of 900℃-950℃, the solute atoms in the ingot are fully diffused and redistributed, thereby eliminating the element segregation problem that may occur during the casting process; at the same time, reasonable high-temperature annealing treatment can reduce the internal stress of the ingot, improve casting defects, and enhance the structural stability of the material. The holding time of 4h-6h provides sufficient diffusion time for further homogenization of the composition, while avoiding the problem of abnormal grain growth that may be caused by excessively long holding time. Through the homogenization annealing process, the internal structure of the ingot is transformed from the original cast structure to a uniform and dense solid solution structure, which not only provides high-quality billet for the subsequent forging process, but also improves the plasticity and processing properties of the material, and reduces the risk of cracks and defects during the forging process.
[0023] Preferably, in the forging process of step 4, the forging die is a 20 mm cylindrical die.
[0024] Through the above technical solution, a 20mm cylindrical die is preferably used in the forging process, which effectively optimizes the plastic deformation behavior of the material during the forging process. By controlling the size of the die, the ingot is gradually forged into a cylindrical rod with a diameter of 20mm. This specification is not only suitable for subsequent heat treatment and processing steps, but also can significantly improve the density of the material during the forging process, eliminate casting defects, and improve the internal structure of the material.
[0025] Preferably, in the solution treatment process of step five, the solution treatment temperature is 900° C.-980° C., the holding time is 1 h-5 h, and then rapid water cooling is performed.
[0026] The above technical solution allows the full dissolution of alloying elements such as chromium, zirconium, magnesium, silicon, and hafnium into the copper matrix, and rapid water cooling results in a uniform, supersaturated solid solution alloy. This temperature range ensures the full dissolution of strengthening elements and their retention at room temperature while also avoiding problems such as grain growth or element burnout caused by excessively high temperatures. A reasonable holding time of 1 to 5 hours provides sufficient diffusion time for the solute elements to be evenly distributed in the matrix, further improving the alloy's compositional uniformity and structural stability.
[0027] Preferably, in the pre-aging treatment process of step six, the temperature is 400° C.-500° C. and the holding time is 3 h-5 h.
[0028] Through the above technical solution, in the pre-aging treatment process, the treatment temperature is preferably set to 400℃-500℃, and the holding time is 3h-5h. Through the reasonable design of this parameter, the alloy material after solid solution treatment can precipitate the second phase at an appropriate temperature, thereby introducing a preliminary precipitation strengthening effect. This pre-aging temperature range ensures the uniformity and small size of the precipitated phase, while avoiding the problems of coarsening of the precipitated phase due to excessively high temperature or insufficient precipitation of the second phase due to excessively low temperature. The holding time is controlled between 3h-5h, providing sufficient time to promote the precipitation and uniform distribution of solute atoms from the matrix, further improving the structural stability of the material.
[0029] Preferably, in the first drawing process of step seven, the drawing speed is 20-45 m / min, multiple drawing passes are performed, the drawing strain of each pass is 0.1-0.15, and the diameter of the alloy wire is 9 mm-11 mm. In the second drawing process of step nine, the drawing speed is 20-45 m / min, and after multiple drawing passes, the drawing strain of each pass is 0.1-0.15, and the diameter of the alloy wire is 5-8 mm.
[0030] Through the above technical solution, the alloy wire can achieve gradual and precise size control and further optimization of structure while taking into account processing efficiency and material properties;
[0031] In the first drawing process, the drawing speed is preferably 20-45m / min, and multiple drawing passes are used, with the drawing strain of each pass controlled within the range of 0.1-0.15, to finally process the alloy rod from 20mm to a wire with a diameter of 9mm-11mm. This process design ensures the processing efficiency of the material at a higher drawing speed. At the same time, the reasonable single-pass strain effectively avoids the problems of work hardening and internal stress concentration caused by excessive deformation, ensuring the continuity and dimensional accuracy of the wire. In addition, by gradually reducing the wire diameter and combining it with appropriate pre-aging treatment, the distribution of the strengthening phase in the matrix is more uniform, laying a good organizational foundation for subsequent processing;
[0032] In the second drawing process, the drawing speed is also 20-45m / min, and the wire diameter is further reduced from 9mm-11mm to 5mm-8mm through multiple drawing passes. The drawing strain of each pass is still controlled within the range of 0.1-0.15 to avoid the risk of material breakage in subsequent processing, while maintaining good surface quality and internal structural uniformity of the wire. The second drawing is carried out after the alloy has undergone secondary aging treatment. At this time, the material has a certain strengthening effect, but still maintains good plasticity and can adapt to further deformation. Through this process design, a wire blank with precise dimensions and dense structure is finally obtained, providing ideal material conditions for the subsequent final third aging treatment.
[0033] Preferably, the second aging treatment process in step eight has an aging temperature of 400°C-500°C and a holding time of 0.5h-4h; the third aging treatment process in step ten has an aging temperature of 400°C-500°C and a holding time of 0.5h-4h.
[0034] Through the above technical solution, the alloy elements in the alloy are fully precipitated and optimally distributed, which improves the mechanical properties and electrical conductivity of the wire.
[0035] During the second aging process, controlling the aging temperature within the 400°C-500°C range and setting a reasonable holding time of 0.5h-4h ensures that solute atoms have ample time and motivation to precipitate and form new second-phase particles at post-drawing vacancies, dislocations, and other crystal defects. This newly formed second phase is evenly distributed around the pre-aged particles and is fine in size, significantly improving the material's yield strength and tensile strength. At this temperature, the precipitation of the precipitated phase at crystal defects such as vacancies and dislocations effectively releases distortion energy, while the matrix undergoes recovery, reducing the dislocation density within the matrix. This results in the material possessing high strength while maintaining good ductility and toughness. This provides excellent processing properties for the subsequent second drawing process and prevents cracking or damage caused by increased brittleness during processing.
[0036] The third aging treatment, using similar process parameters as the second aging treatment, provides final strengthening of the wire after the second drawing. This step focuses on further optimizing the precipitates, eliminating the residual stress introduced by the second drawing, and improving the alloy's microstructure. Through proper aging control, the precipitates within the material achieve an ideal, stable state of dispersed distribution and fine size, further enhancing yield strength and tensile strength while maintaining excellent electrical conductivity. This aging treatment also ensures the consistent performance and long-term stability of the final alloy wire.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. This method for preparing high-strength, high-conductivity Cu-Cr-Zr alloy wire utilizes a microalloying process to add magnesium, silicon, and hafnium alloying elements. This effectively hinders the diffusion of chromium and delays the overaging phenomenon caused by the coarsening of nanoscale chromium particles during heat treatment, thereby significantly improving the alloy's high-temperature stability and precipitation uniformity. Consequently, the present invention offers a broad processing window, maintaining the stability and uniformity of material properties under varying processing conditions, and providing excellent process adaptability for the preparation of high-strength, high-conductivity copper alloys.
[0039] 2. This method for preparing high-strength and high-conductivity Cu-Cr-Zr alloy wire utilizes a solution treatment followed by aging pretreatment-drawing-aging-drawing-aging process, which offers significant advantages over the traditional solution treatment-cold drawing-aging process. During the pre-aging treatment stage after solution treatment, the second phase precipitates slowly and evenly, effectively avoiding performance fluctuations caused by uneven second phase precipitation. During the drawing process after pre-aging, the interaction between the evenly distributed second phase and dislocations is also more uniform, helping to improve the stability of material properties during processing. Post-drawing secondary aging promotes further precipitation of alloying elements along evenly distributed crystal defects, resulting in a more evenly distributed and smaller second phase particle size, significantly improving the alloy's strengthening effect and electrical conductivity. The secondary drawing and tertiary aging treatments allow the remaining dissolved alloying elements to completely precipitate in the second phase, fully integrating the effects of work hardening and precipitation strengthening, further improving the alloy's mechanical properties, and ensuring its electrical conductivity approaches the theoretical optimum. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic flow chart of the present invention. DETAILED DESCRIPTION
[0041] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0042] See also Figure 1 The present invention provides a technical solution: a method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire.
[0043] Specifically:
[0044] Example 1
[0045] Step 1: Place the alloy raw materials in the following proportions into a medium-frequency induction furnace. The alloy raw materials include the following components: 0.39% chromium, 0.24% zirconium, 0.07% magnesium, 0.02% silicon, 0.07% hafnium, and the balance copper. Heat to 1250°C for vacuum melting and hold for 1 hour. Evacuate the furnace and then slowly fill it with high-purity argon at a controlled flow rate of 25L / min until an inert protective atmosphere is formed in the furnace. The pressure is maintained at or slightly above atmospheric pressure. Maintain a continuous flow of argon throughout the melting process.
[0046] Step 2: Casting the alloy obtained in step 1 to obtain a cylindrical ingot, the casting temperature is 1200° C., and the diameter of the cast cylindrical ingot is 90 mm;
[0047] Step 3: homogenizing annealing the cylindrical ingot obtained in step 2, wherein the homogenizing annealing temperature of the obtained cylindrical ingot is 920° C. and the holding time is 5 hours;
[0048] Step 4: Forging the cylindrical ingot obtained in step 3 after surface treatment to obtain the alloy rod, using a 20 mm cylindrical die forging die;
[0049] Step 5: placing the alloy rod obtained in step 4 in a resistance furnace for solution treatment. The obtained alloy rod after solution treatment has a solution treatment temperature of 940°C and a holding time of 4 hours, followed by rapid water cooling.
[0050] Step 6: placing the alloy rod obtained in step 5 in a resistance furnace for pre-aging treatment to obtain a high-strength alloy rod, the pre-aging treatment temperature is 450° C., and the holding time is 4 hours;
[0051] Step 7: The alloy rod obtained in step 6 is drawn for the first time. The diameters of the obtained alloy wires are 20 mm, 18.4 mm, 17.2 mm, 16.0 mm, 15.2 mm, 14.1 mm, 13.2 mm, 12.4 mm, 11.6 mm, and 11.0 mm, respectively. The drawing speed is 35 m / min, and multiple drawing passes are performed, with a drawing strain of 0.125 in each pass.
[0052] Step 8: placing the alloy wire obtained in step 7 in a resistance furnace for a second aging treatment, wherein the aging temperature of the obtained alloy wire is 450° C. and the aging time is 1 hour;
[0053] After cooling the aged alloy wire obtained in step eight, a finished Cu-Cr-Zr alloy wire was obtained. The test data of the product is shown in Table 1.
[0054] Table 1
[0055]
[0056] Example 2
[0057] Step 1: Place the alloy raw materials in the following proportions into a medium-frequency induction furnace. The alloy raw materials include the following components: 0.39% chromium, 0.24% zirconium, 0.07% magnesium, 0.02% silicon, 0.07% hafnium, and the balance copper. Heat to 1250°C for vacuum melting and hold for 1 hour. Evacuate the furnace and then slowly fill it with high-purity argon at a controlled flow rate of 25L / min until an inert protective atmosphere is formed in the furnace. The pressure is maintained at or slightly above atmospheric pressure. Maintain a continuous flow of argon throughout the melting process.
[0058] Step 2: Casting the alloy obtained in step 1 to obtain a cylindrical ingot, the casting temperature is 1200° C., and the diameter of the cast cylindrical ingot is 90 mm;
[0059] Step 3: homogenizing annealing the cylindrical ingot obtained in step 2, wherein the homogenizing annealing temperature of the obtained cylindrical ingot is 920° C. and the holding time is 5 hours;
[0060] Step 4: Forging the cylindrical ingot obtained in step 3 after surface treatment to obtain the alloy rod, using a 20 mm cylindrical die forging die;
[0061] Step 5: placing the alloy rod obtained in step 4 in a resistance furnace for solution treatment. The obtained alloy rod after solution treatment has a solution treatment temperature of 940°C and a holding time of 4 hours, followed by rapid water cooling.
[0062] Step 6: placing the alloy rod obtained in step 5 in a resistance furnace for pre-aging treatment to obtain a high-strength alloy rod, the pre-aging treatment temperature is 450° C., and the holding time is 4 hours;
[0063] Step 7: The alloy rod obtained in step 6 is drawn for the first time. The diameters of the obtained alloy wires are 20 mm, 18.4 mm, 17.2 mm, 16.0 mm, 15.2 mm, 14.1 mm, 13.2 mm, 12.4 mm, 11.6 mm, and 11.0 mm, respectively. The drawing speed is 35 m / min, and 9 drawing passes are performed. The drawing strain of each pass is 0.125.
[0064] Step 8: placing the alloy wire obtained in step 7 in a resistance furnace for a second aging treatment, wherein the aging temperature of the obtained alloy wire is 500° C. and the aging time is 0.5 h;
[0065] Step 9: The alloy wire obtained in step 8 is drawn for the second time. The diameters of the alloy wire obtained after the second drawing are 11.0 mm, 10.2 mm, 9.60 mm, 8.97 mm, 8.48 mm, and 8.00 mm, respectively. The drawing speed is 35 m / min, and the drawing is performed 5 times. The drawing strain of each time is 0.125.
[0066] Step 10: The alloy wire obtained in step 9 is aged for the third time. The alloy finished product obtained after surface treatment is a high-conductivity and high-strength alloy wire. The aging temperature is 500° C. and the aging time is 0.5 h.
[0067] After cooling the aged alloy wire obtained in step 10, a finished Cu-Cr-Zr alloy wire is obtained. The test data of the product is shown in Table 2.
[0068] Table 2
[0069]
[0070]
[0071] Example 3
[0072] Step 1: Place the alloy raw materials in the following proportions into a medium-frequency induction furnace. The alloy raw materials include the following components: 0.40% chromium, 0.20% zirconium, 0.10% magnesium, 0.05% silicon, 0.2% hafnium, and the balance copper. Heat to 1250°C for vacuum melting and hold for 1 hour. Evacuate the furnace and then slowly fill it with high-purity argon at a controlled flow rate of 25L / min until an inert protective atmosphere is formed in the furnace. The pressure is maintained at or slightly above atmospheric pressure. Maintain a continuous flow of argon throughout the melting process.
[0073] Step 2: Casting the alloy obtained in step 1 to obtain a cylindrical ingot, the casting temperature is 1200° C., and the diameter of the cast cylindrical ingot is 90 mm;
[0074] Step 3: homogenizing annealing the cylindrical ingot obtained in step 2, wherein the homogenizing annealing temperature of the obtained cylindrical ingot is 940° C. and the holding time is 4 hours;
[0075] Step 4: Forging the cylindrical ingot obtained in step 3 after surface treatment to obtain the alloy rod, using a 20 mm cylindrical die forging die;
[0076] Step 5: placing the alloy rod obtained in step 4 in a resistance furnace for solution treatment. The obtained alloy rod after solution treatment has a solution treatment temperature of 960°C and a holding time of 2 hours, followed by rapid water cooling.
[0077] Step 6: placing the alloy rod obtained in step 5 in a resistance furnace for pre-aging treatment to obtain a high-strength alloy rod, the pre-aging treatment temperature is 450° C., and the holding time is 4 hours;
[0078] Step 7: The alloy rod obtained in step 6 is drawn for the first time. The diameters of the obtained alloy wires are 20 mm, 18.4 mm, 17.2 mm, 16.0 mm, 15.2 mm, 14.1 mm, 13.2 mm, 12.4 mm, 11.6 mm, and 11.0 mm, respectively. The drawing speed is 35 m / min, and 9 drawing passes are performed. The drawing strain of each pass is 0.125.
[0079] Step 8: placing the alloy wire obtained in step 7 in a resistance furnace for a second aging treatment, wherein the aging temperature of the obtained alloy wire is 450° C. and the aging time is 1 hour;
[0080] Step 9: The alloy wire obtained in step 8 is drawn for the second time. The diameters of the alloy wire obtained after the second drawing are 11.0 mm, 10.2 mm, 9.60 mm, 8.97 mm, 8.48 mm, and 8.00 mm, respectively. The drawing speed is 35 m / min, and the drawing is performed 5 times. The drawing strain of each time is 0.125.
[0081] Step 10: The alloy wire obtained in step 9 is aged for the third time. After surface treatment, the alloy product is a high-conductivity and high-strength alloy wire. The aging temperature is 450° C. and the aging time is 1 hour.
[0082] After cooling the aged alloy wire obtained in step 10, a finished Cu-Cr-Zr alloy wire is obtained. The test data of the product is shown in Table 3.
[0083] Table 3
[0084]
[0085]
[0086] Example 4
[0087] Step 1: Place the alloy raw materials in the following proportions into a medium-frequency induction furnace. The alloy raw materials include the following components: 0.35% chromium, 0.15% zirconium, 0.02% magnesium, 0.01% silicon, 0.12% hafnium, and the balance copper. Heat to 1250°C for vacuum melting and hold for 1 hour. Evacuate the furnace and then slowly fill it with high-purity argon at a controlled flow rate of 25L / min until an inert protective atmosphere is formed in the furnace. The pressure is maintained at or slightly above atmospheric pressure. Maintain a continuous flow of argon throughout the melting process.
[0088] Step 2: Casting the alloy obtained in step 1 to obtain a cylindrical ingot, the casting temperature is 1200° C., and the diameter of the cast cylindrical ingot is 90 mm;
[0089] Step 3: homogenizing annealing the cylindrical ingot obtained in step 2, wherein the homogenizing annealing temperature of the obtained cylindrical ingot is 960° C. and the holding time is 6 hours;
[0090] Step 4: Forging the cylindrical ingot obtained in step 3 after surface treatment to obtain the alloy rod, using a 20 mm cylindrical die forging die;
[0091] Step 5: placing the alloy rod obtained in step 4 in a resistance furnace for solution treatment. The obtained alloy rod after solution treatment has a solution treatment temperature of 940°C and a holding time of 4 hours, followed by rapid water cooling.
[0092] Step 6: placing the alloy rod obtained in step 5 in a resistance furnace for pre-aging treatment to obtain a high-strength alloy rod, the pre-aging treatment temperature is 400°C, and the holding time is 5 hours;
[0093] Step 7: The alloy rod obtained in step 6 is drawn for the first time. The diameters of the obtained alloy wires are 20 mm, 18.4 mm, 17.2 mm, 16.0 mm, 15.2 mm, 14.1 mm, 13.2 mm, 12.4 mm, 11.6 mm, and 11.0 mm, respectively. The drawing speed is 35 m / min, and 9 drawing passes are performed. The drawing strain of each pass is 0.125.
[0094] Step 8: placing the alloy wire obtained in step 7 in a resistance furnace for a second aging treatment, wherein the aging temperature of the obtained alloy wire is 400° C. and the aging time is 4 hours;
[0095] Step 9: The alloy wire obtained in step 8 is drawn for the second time. The diameters of the alloy wire obtained after the second drawing are 11.0 mm, 10.2 mm, 9.60 mm, 8.97 mm, 8.48 mm, and 8.00 mm, respectively. The drawing speed is 35 m / min, and the drawing is performed 5 times. The drawing strain of each time is 0.125.
[0096] Step 10: The alloy wire obtained in step 9 is aged for the third time. After surface treatment, the alloy product is a high-conductivity and high-strength alloy wire. The aging temperature is 400° C. and the aging time is 4 hours.
[0097] After cooling the aged alloy wire obtained in step 10, a finished Cu-Cr-Zr alloy wire is obtained. The test data of the product is shown in Table 4.
[0098] Table 4
[0099]
[0100] In summary, Example 1 shows that the comprehensive performance of the Cu-Cr-Zr alloy that has undergone only one drawing deformation and aging treatment is relatively low. The results of Examples 2, 3, and 4 compared with Example 1 show that the Cu-Cr-Zr alloy wire obtained by multi-stage thermomechanical treatment has a tensile strength of more than 575 MPa, a yield strength of more than 550 MPa, a Vickers hardness of more than 170 HV, and an electrical conductivity of more than 78% IACS, and has high comprehensive performance. This shows that the present invention, by designing a multi-stage thermomechanical treatment method, prepares a Cu-Cr-Zr alloy with high strength and conductivity, and can be effectively controlled in industrial production.
Claims
1. A method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire, comprising the following steps: The alloy raw material comprises the following components by mass percentage: 0.30%-0.40% chromium, 0.1%-0.25% zirconium, 0.02%-0.12% magnesium, 0.01%-0.05% silicon, 0.05%-0.25% hafnium, and the balance is copper and unavoidable impurities; Step 1: Put the alloy raw materials into the melting furnace according to the proportion for vacuum melting; Step 2: Casting the liquid molten alloy obtained in step 1 to obtain a cylindrical ingot; Step 3: performing homogenization annealing treatment on the cylindrical ingot obtained in step 2 to obtain a homogenized cylindrical ingot; Step 4: performing die forging after surface treatment on the cylindrical ingot obtained in step 3 to obtain an alloy rod; Step 5: subjecting the alloy rod obtained in step 4 to solid solution treatment to obtain a solid solution treated alloy rod; Step 6: Performing a pre-aging treatment on the alloy rod obtained in step 5 to obtain an alloy rod with a certain strength; Step 7: Drawing the alloy rod obtained in step 6 for the first time to obtain an alloy wire; Step 8: subjecting the alloy wire obtained in step 7 to a second aging treatment to obtain an aged alloy wire; Step nine: Drawing the alloy wire obtained in step eight for a second time to obtain a second drawn alloy wire; Step 10: subjecting the alloy wire obtained in step 9 to a third aging treatment, and obtaining the alloy finished product after surface treatment to obtain a high-strength and high-conductivity alloy wire.
2. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the vacuum melting process of step 1, the melting temperature is 1200-1400°C, the holding time is 0.5h-2h, the melting furnace is evacuated to vacuum, and then high-purity argon is slowly filled in, and the argon flow rate is controlled at 10-50L / min until an inert protective atmosphere is formed in the furnace, and the pressure is maintained at or slightly above normal pressure. During the entire melting process, the continuous flow of argon is maintained.
3. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the casting process of step 2, the casting temperature is 1100° C.-1300° C., and the diameter of the cast cylindrical ingot is 90 mm.
4. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the homogenization annealing process of step three, the treatment temperature is 900°C-950°C and the holding time is 4h-6h.
5. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the forging process of step 4, the forging die adopts a 20 mm cylindrical die.
6. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the solution treatment process of step five, the solution treatment temperature is 900°C-980°C and the holding time is 1h-5h.
7. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: The pre-aging treatment process in step six is performed at a temperature of 400°C-500°C and a holding time of 3h-5h.
8. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: In the first drawing process of step seven, the drawing speed is 20-45m / min, multiple drawing passes are performed, the drawing strain of each pass is 0.1-0.15, and the diameter of the alloy wire is 9mm-11mm. In the second drawing process of step nine, the drawing speed is 20-45m / min, and multiple drawing passes are performed, the drawing strain of each pass is 0.1-0.15, and the diameter of the alloy wire is 5-8mm.
9. The method for preparing a high-strength and high-conductivity Cu-Cr-Zr alloy wire according to claim 1, characterized in that: The second aging treatment process of step eight has an aging temperature of 400-500°C and a holding time of 0.5-4h; the third aging treatment process of step ten has an aging temperature of 400-500°C and a holding time of 0.5h-4h.
Citation Information
Patent Citations
Preparation method of CuCrZr alloy
CN105925922A
High-plasticity, high-strength and high-conductivity CuCrZr series copper alloy and preparation method thereof
CN110747365A
Method for preparing CuCrZr alloy through two-stage aging process
CN113832367A
A method for preparing CuCrZr alloys using a two-stage aging process
CN113832367B
High-strength and high-conductivity copper alloy for contact line and preparation method of high-strength and high-conductivity copper alloy
CN105088001A